2014
DOI: 10.1186/1742-4690-11-36
|View full text |Cite
|
Sign up to set email alerts
|

Novel principles of gamma-retroviral insertional transcription activation in murine leukemia virus-induced end-stage tumors

Abstract: BackgroundInsertional mutagenesis screens of retrovirus-induced mouse tumors have proven valuable in human cancer research and for understanding adverse effects of retroviral-based gene therapies. In previous studies, the assignment of mouse genes to individual retroviral integration sites has been based on close proximity and expression patterns of annotated genes at target positions in the genome. We here employed next-generation RNA sequencing to map retroviral-mouse chimeric junctions genome-wide, and to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
24
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 102 publications
2
24
0
1
Order By: Relevance
“…Other studies have reported integrations of hepatitis B virus and human papillomavirus DNAs in the TERT promoter region in human liver and cervical tumors, resulting in elevated TERT expression (44). While sense and antisense retroviral activation has been previously reported (1,41), to our knowledge, this is the first report of retroviral activation of a bidirectional promoter-associated lncRNA. In this work, we show that most of the proviral integrations in our tumors are in the antisense direction relative to TERT and drive the overexpression of a novel lncRNA transcribed from a bidirectional promoter.…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…Other studies have reported integrations of hepatitis B virus and human papillomavirus DNAs in the TERT promoter region in human liver and cervical tumors, resulting in elevated TERT expression (44). While sense and antisense retroviral activation has been previously reported (1,41), to our knowledge, this is the first report of retroviral activation of a bidirectional promoter-associated lncRNA. In this work, we show that most of the proviral integrations in our tumors are in the antisense direction relative to TERT and drive the overexpression of a novel lncRNA transcribed from a bidirectional promoter.…”
Section: Discussionmentioning
confidence: 56%
“…Retroviruses can induce overexpression of host genes by multiple mechanisms (1,41). For instance, insertion of viral enhancer elements in the vicinity of host gene promoters can induce overexpression (1).…”
Section: Resultsmentioning
confidence: 99%
“…In contrast to integrations in shortterm cell culture, where one expects little selection, tumours ex vivo have undergone strong selection for cell growth. In mouse end-stage tumours, irrespective of the distance to transcription start sites, the majority of integrations colocalized with common epigenetic enhancer markers in murine lymphoid tissues (Akagi et al, 2004;Sokol et al, 2014;Uren et al, 2008). Of 6132 tags we analysed previously in T lymphomas induced by exogenous MLV, 46.4 % were in genes.…”
Section: Passenger Integrations Versus Drivers Of Tumorigenesismentioning
confidence: 98%
“…In addition to the names of the genes, Table 2 lists the location of the insertions in or near the genes and the layout of the insertions. A separate column gives the number of additional insertions at a given locus in lymphomas recovered by us, or in lymphocytic/ myeloid tumours reported by others (Akagi et al, 2004;Sokol et al, 2014;Uren et al, 2008). Because the insertions were absent from the BALB/c-generated fusion Table 2.…”
Section: De Novo Insertions In B/w Spleen Cellsmentioning
confidence: 99%
“…The presence of retroviral sequence similar to gene fusions produces sequence signatures across the genome, and such signatures can be exploited to determine the orientation as well as the exact positions of endogenous and exogenous retroviruses if the chimeric junction, that is, the point of fusion with host flanking sequence, is covered in sequencing. Using paired‐end RNA‐seq in whole‐transcriptome analyses of mouse tumors we showed that integration of exogenous gamma‐retroviruses are exposed by at least one of 14 paired‐end sequence signatures that permit detection of multiple modes of insertional mutagenesis such as promoter insertion and antisense transcription (Fig. ) .…”
Section: Genome‐wide Mapping Of Chimeric Regions Using Paired‐end Rnamentioning
confidence: 99%